DIVERSITY OF PISCES IN THE LEMBAH TUMPANG - Murti, Aisyah Andhina; Ayu, Fatma Aisyah; Nisa, Hafidzah Ra'iyatun; Mukti, Nuril Chasanah; Maudina, Rahma Ursula; Fardani, Indra; Qomaliyah, Eka Nurul (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
The objective of this study was to determine the diversity of fish species found in Tumpang Valley, Tumpang Sub-district, Malang Regency, East Java as an effort to preserve fish species. The method used in this research is observation in various ponds by using the help of reflection book and google lens to identify the types of fish found. Based on the results of research conducted by researchers on the diversity of fish species in Tumpang Resort Valley Area, Tumpang District, Malang Regency, the results indiccate that there are 5 species, namely koi fish, Javanese wader fish (tawes), tilapia fish, citul fish, and goldfish. There are various types of koi fish with different genetic variations, but there are 8 koi fish that can be identified by researchers, namely platinum koi fish, orenji ogon koi fish, karasugoi koi fish, kigoi koi fish, yamato nishiki koi fish, nezu ogon koi fish, silver koi fish, and sanke koi fish. The result of the fish diversity index obtained is 1.173 (in the low category).